Simplicius on the Planets and Their Motions : In Defense of a Heresy. - Bowen, Alan C. (Philosophia antiqua., 2012)
The book contends that the digression ending Simplicius' In de caelo 2.12 is not a proper history of early Greek planetary theory, but a creative attempt to show that to accept Ptolemy's planetary hypotheses one need not repudiate Aristotle's argument that the cosmos is eternal.